Disentangling magnetic and environmental signatures of sedimentary 10Be/9Be records - Savranskaia, Tatiana; Egli, Ramon; Valet, Jean-pierre; Bassinot, Franck; Meynadier, Laure; Bourlès, Didier L.; Simon, Quentin; Thouveny, Nicolas (Quaternary Science Reviews, 2021)
Reconstructions of the global production rate of the cosmogenic isotope 10Be from sedimentary records of authigenic 10Be/9Be ratios have been successfully used to obtain independent estimates of geomagnetic dipole moment variations caused by field excursions or reversals. In this study, we assess the reliability of 10Be/9Be as a proxy for the cosmogenic 10Be production rate by evaluating two potential biasing sources represented by sediment composition and climatic modulation. For this purpose, we compare five high-resolution 10Be/9Be records of the Matuyama-Brunhes (M-B) field reversal from sediment cores of the Indian, West Pacific, and North Atlantic oceans. Significant increase of 10Be/9Be ratios at 774 ka is explained in terms of the dominant control of geomagnetic modulation during the M-B reversal. Results do not support the existence of a direct proportionality between measured sedimentary 10Be/9Be ratio and cosmogenic 10Be production rate, as shown by 10Be/9Be records that offset relative to each other during and outside the M-B reversal. Residual differences between offset-corrected rescaled records do not appear to be related to an incomplete correction of variable sediment scavenging efficiencies by 9Be normalization. Instead, these differences can be explained by a common climatic modulation model, assuming a linear relation between 10Be/9Be and the global 10Be production rate with site- and time-dependent additive and multiplicative coefficients. These coefficients are linear functions of a single global climate proxy identified with the benthic O record. Additive coefficients are almost constant in time and can represent up to 60% of the average 10Be/9Be value during periods of stable field polarity. Multiplicative coefficients are also site-specific, with mean values representing the bulk scavenging efficiency of the site, and variations about this mean expressing a multiplicative climatic modulation of the 10Be production rate. The amplitude of this modulation amounts to 10–15% of the maximum ...